Modification method of kaolin and adsorbent

By in-situ modification of the kaolin surface, adjusting its isoelectric point and specific surface area, and forming an efficient adsorbent, the problem of unstable kaolin modification performance in the prior art is solved, and efficient adsorption of heavy metal ions and the expansion of various application fields is achieved.

CN119503822APending Publication Date: 2025-02-25NINGBO JIANRONG SPECIAL SEPARATION MEMBRANE TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411682586.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing kaolin modification methods are modified through non-chemical methods, resulting in unstable performance of composite materials and insufficient adsorption capacity, making it difficult to broaden the application fields of kaolin.

Method used

By in-situ modification of the kaolin surface, chemical reagents such as ethyl silicate and ammonia water are used to adjust the isoelectric point and specific surface area of ​​the kaolin to form an efficient adsorbent.

Benefits of technology

It has improved the adsorption and dispersion ability of kaolin to moisture, ions, pigments and other substances, and improved the adsorption ability of heavy metal ions. It is suitable for wastewater treatment, groundwater repair and chemical separation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119503822A_ABST
    Figure CN119503822A_ABST
Patent Text Reader

Abstract

The invention discloses a kaolin modification method and an adsorbent, and belongs to the technical field of silicon compounds, the method comprises the following steps: adding water, ethyl silicate and kaolin while stirring, and adjusting the pH value to 1.5-3.5 to obtain a first liquid; adding ammonia water into the first liquid for reaction; and after the reaction, filtering and separating, and drying and crushing the solid to obtain the adsorbent. By carrying out in-situ modification on the surface of the kaolin, the isoelectric point and the specific surface area of the kaolin are adjusted, and the adsorption and dispersion capacities of the kaolin on substances such as water, ions and pigments can be improved; the adsorption capacity on heavy metal ions can be improved, and the adsorbent can be used for sewage treatment; and the composite material can be applied to the application fields of groundwater remediation or chemical separation and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of silicon compounds, and in particular to a kaolin modification method and an adsorbent. Background Art

[0002] Kaolin is an important mineral resource, commonly used in industries such as ceramics, coatings, plastics and cosmetics. By changing the electrical properties of kaolin in solution, its adsorption, bonding and stability properties can be affected.

[0003] Modifying kaolin to improve adsorption performance has become an important research direction. The main methods at present are: constructing composite materials through kaolin, such as kaolin-nano Fe2O3-lignin hydrogel composites, kaolin-based hydrotalcite composites, nano-flaky kaolin-wollastonite-hydroxy silicone oil ternary composite powders, and nano-ZnO / kaolin composite antibacterial materials. However, the above methods are modified by non-chemical means, and the combination of the various components in the composite material is relatively loose, and stratification is easily produced between the materials, resulting in unstable performance of the modified products.

[0004] Therefore, it is necessary to design a modification method to improve the adsorption capacity of kaolin, so as to broaden the application field of kaolin and enable it to play a greater role in environmental protection and resource utilization. Summary of the invention

[0005] In view of the above technical problems existing in the prior art, the present invention provides a kaolin modification method and an adsorbent, which improve the adsorption capacity by in-situ modification of the kaolin surface.

[0006] The invention discloses a method for modifying kaolin, comprising the following steps: adding water, ethyl silicate and kaolin under stirring, and adjusting the pH to 1.5-3.5 to obtain a first liquid; adding ammonia water to the first liquid for reaction; after the reaction, filtering and separating, drying and crushing the solid to obtain an adsorbent.

[0007] Preferably, the amount of ethyl silicate added is: 2-49wt%;

[0008] The amount of kaolin added is: 40-50wt%; the amount of water added is: 0.6-2.5wt%; the amount of ammonia water added is: 1-2wt%.

[0009] Preferably, the method specifically comprises the following steps:

[0010] 2.2 wt % of purified water, 48.1 wt % of ethyl silicate, and 48.1 wt % of kaolin were added under stirring at room temperature, and hydrochloric acid was added and stirred for 1-3 hours, and then the pH of the solution was adjusted to 1.5-3.5 to obtain a first liquid;

[0011] After stirring for about 3 hours, add 1.6% ammonia water, and continue stirring for 1-2 hours;

[0012] After the reaction was completed, the solid was separated by filtration and then dried and crushed to obtain an adsorbent.

[0013] Preferably, 1-78.1 wt % of dimethylacetamide is also added to the first liquid.

[0014] Preferably, the method specifically comprises: adding 0.6-1wt% purified water, 10-47.3wt% dimethylacetamide, 23.6-41wt% ethyl silicate, and 26.7-46wt% kaolin under stirring at room temperature, and after stirring for one hour, adding hydrochloric acid to adjust the solution to pH 1.9-3 to obtain a first liquid;

[0015] Continue stirring the first liquid for 5-8 hours, then let it stand for 30-40 hours, stir and add 1-1.8% ammonia water, and react for 1-2 hours;

[0016] After the reaction was completed, the solid was separated by filtration and then dried and crushed to obtain an adsorbent.

[0017] Preferably, the method specifically comprises: adding dimethylacetamide and polyvinyl pyrrolidone with stirring at room temperature, stirring until the liquid becomes transparent, to obtain a second liquid;

[0018] Add water, ethyl silicate and kaolin at room temperature (20-30° C.) with stirring, add hydrochloric acid and stir for 2 hours, then adjust the solution to pH 3 to obtain a third liquid;

[0019] After continuing to stir for about 3 hours, the second liquid and the third liquid are mixed in proportion, and then slowly stirred for about 13 hours to obtain a first liquid;

[0020] adding aqueous ammonia to the first liquid to react;

[0021] After the reaction was completed, the solid was separated by filtration and then dried and crushed to obtain an adsorbent.

[0022] Preferably, the second liquid contains 47-78.7 wt % of dimethylacetamide, and the balance is polyvinyl pyrrolidone;

[0023] The third liquid contains 0.6-2.5wt% of water, 2-49wt% of ethyl silicate, and 40-50wt% of kaolin.

[0024] Preferably, the weight ratio of the second liquid to the third liquid is 0.1-0.3:1.

[0025] The present invention also provides an adsorbent prepared by the method.

[0026] Preferably, the adsorbent has an isoelectric point of pH 1.5-4.6 and a specific surface area of ​​35-103m 2 / g; the adsorbent is used for sewage treatment.

[0027] Compared with the prior art, the beneficial effects of the present invention are as follows: by in-situ modification of the kaolin surface and adjusting the isoelectric point and specific surface area of ​​kaolin, its adsorption and dispersion capabilities for water, ions, pigments and other substances can be improved; the adsorption capacity for heavy metal ions can be increased, and it can be used for sewage treatment; the adsorption of organic matter can also be enhanced, and it can be used in application fields such as groundwater remediation or separation of chemicals. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 is a flow chart of the modification method of kaolin of the present invention;

[0029] Figure 2 is a graph of the zeta potential of the adsorbent and pH. DETAILED DESCRIPTION

[0030] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] The present invention is further described in detail below in conjunction with the accompanying drawings:

[0032] The first aspect of the present invention provides a method for modifying kaolin, such as Figure 1 , including the following steps:

[0033] Step 101: Add water, ethyl silicate and kaolin under stirring, and adjust the pH to 1.5-3.5 to obtain a first liquid.

[0034] Step 102: adding ammonia water to the first liquid for reaction.

[0035] Step 103: After the reaction, filter and separate, dry and crush the solid to obtain an adsorbent. The solid can also be washed with water and then filtered and dried.

[0036] By in-situ modification of the kaolin surface and adjusting the isoelectric point and specific surface area of ​​kaolin, its adsorption and dispersion capabilities for water, ions, pigments and other substances can be improved; the adsorption capacity for heavy metal ions can be increased and can be used for sewage treatment; the adsorption of organic matter can also be enhanced and used in application areas such as groundwater remediation or chemical separation.

[0037] The experimental materials used in the present invention are as follows: kaolin, grade one, purity 93.7%, 2500 mesh, white, provided by Lingshou Yixin Mineral Products Processing Factory. Polyvinyl pyrrolidone (PvpK30) was provided by Boai Xinkaiyuan Pharmaceutical Co., Ltd. Tetraethyl orthosilicate-28 (TEOS), completely hydrolyzed SiO2 content: 28.28%, provided by Zhangjiagang Jinshilun Chemical Technology Co., Ltd. Concentrated hydrochloric acid, HCl content: 28%. Ammonia water, NH3 content: 25-28%. Dimethylacetamide (DMAC) was provided by Zhejiang Sunrise Fine Chemical Co., Ltd.

[0038] Example 1

[0039] Step 201: add purified water: 0.6% (weight percentage, the same below), DMAC: 47.3%, TEOS: 23.6%, kaolin: 26.7% under stirring at room temperature (20-30° C.), stir for one hour, and then add hydrochloric acid to adjust the solution to pH 1.9.

[0040] Step 202: After continuing to stir for about 7 hours, the liquid is left to stand for about 40 hours, and then 1.8% ammonia water is added with stirring. Stirring is continued until TEOS undergoes polymerization reaction, which lasts about one hour.

[0041] Step 203: After the reaction is completed, the solid is separated by filtration, and then dried and crushed to obtain adsorbent 1.

[0042] Example 2

[0043] Step 301: add 1% purified water, 10.2% DMAC, and 40.8% TEOS at room temperature (20-30° C.) with stirring, and add hydrochloric acid to adjust the solution to pH 3 after stirring for about 30 minutes.

[0044] Step 302: After adding 1% of pure water, add 46% of kaolin, continue stirring for about 6 hours, let it stand for about 14 hours, then add 1% of ammonia water, continue stirring until TEOS undergoes polymerization, about one hour.

[0045] Step 303: After the reaction is completed, the solid is separated by filtration, and then dried and crushed to obtain adsorbent 2.

[0046] Example 3

[0047] Step 401: add 2.2% purified water, 48.1% TEOS, and 48.1% kaolin at room temperature (20-30° C.) with stirring, add hydrochloric acid and stir for 2 hours to adjust the solution to pH 3 to obtain a first liquid.

[0048] Step 402: After continuing stirring for about 3 hours, add 1.6% ammonia water, and then continue stirring until TEOS undergoes polymerization reaction, which lasts about one hour.

[0049] Step 403: After the reaction is completed, the solid is separated by filtration, and then dried and crushed to obtain adsorbent 3.

[0050] Example 4

[0051] Step 501: DMAC: 78.7%, PvpK30: 21.3% are added under stirring at room temperature (20-30° C.), and stirred until the liquid becomes transparent to obtain a second liquid (liquid A).

[0052] Step 502: add purified water: 2.2%, TEOS: 48.1%, kaolin: 48.1% at room temperature (20-30° C.) with stirring, add hydrochloric acid and stir for 2 hours to adjust the solution to pH 3 to obtain a third liquid (liquid B).

[0053] Step 503: After continuing to stir for about 3 hours, liquid A is mixed into liquid B at a weight ratio of 0.14, and then slowly stirred for about 13 hours to obtain a first liquid.

[0054] Step 504: After adding 1.5% (based on the total weight of liquid A and liquid B) of aqueous ammonia, continue stirring until TEOS undergoes polymerization reaction, which lasts for about one hour.

[0055] Step 505: After the reaction is completed, the solid is separated by filtration, and then dried and crushed to obtain adsorbent 4.

[0056] The zeta potential of the above-mentioned adsorbent in different pH solutions is shown in Table 1. The kaolin in the present invention is washed kaolin and has not been calcined. The -OH group on the surface of kaolin has the conditions to produce dealcohol polymerization reaction with the Si-C2H5 group of TEOS and dehydration polymerization reaction with the hydrolyzed Si-OH group. In the above embodiments, the hydrolysis reaction under acidic conditions is started, because the hydrolysis reaction mechanism under acidic conditions is electrophilic addition, and the hydrolysis reaction can be completed quickly in a short time. However, the acidic environment also slows down the speed of the subsequent polymerization reaction. For this reason, ammonia water is used as a catalyst to increase the speed of the polymerization reaction. The hydrolyzed Si-OH reacts on the surface of kaolin to form silicon oxide mainly composed of silicon dioxide. Since TEOS is almost completely hydrolyzed before the polymerization reaction occurs, the main form of chemical reaction on the surface of kaolin is dehydration polymerization reaction.

[0057] Table 1

[0058]

[0059] As can be seen from Table 1, the amount of DMAC has a significant impact on the movement of the isoelectric point. The pH corresponding to the zeta potential of zero is taken as the isoelectric point. The pH and isoelectric point at which the zeta potential is zero are obtained by linear insertion method with the two points closest to the positive and negative changes of the zeta potential, and the results are listed in Table 2; Table 2 also shows the specific surface area of ​​the adsorbent. As can be seen from Table 2, compared with the isoelectric point pH 6 of unmodified kaolin, the isoelectric point of adsorbent 1 is close to that of high kaolin, and the isoelectric point decreases as the amount of DMAC added decreases. In Example 3, there is no addition of DMAC, and the isoelectric point is greatly reduced to pH 1.5. As can be seen from adsorbent 4: when DMAC and PvpK30 are present at the same time, although the amount of DMAC added is very high, the isoelectric point is also reduced to pH 1.5, indicating that PvpK30 reduces the negative impact of DMAC.

[0060] Table 2

[0061]

[0062] The present invention modifies kaolin to prepare an adsorbent that can play a greater role in removing heavy metal ions from wastewater. The increase in the surface area of ​​the adsorbent is an important evaluation index. As can be seen from Table 2, the specific surface area of ​​adsorbents 2 and 3 is significantly improved. The improvement of the comprehensive index in Example 3 is the most obvious, and its isoelectric point is reduced from pH 6 to pH 1.5, which is close to the lower limit of the isoelectric point of metal oxides; the specific surface area of ​​the adsorbent is increased from 2.86 to 96.3 m 2 / g, an increase of 33 times! From the amount of TEOS and kaolin added in Example 3, it can be inferred that the theoretical value of the additional silicon dioxide content in the modified kaolin will not be higher than 22%. At the same time, it can be reasonably assumed that the surface of kaolin is completely covered by the additional silicon dioxide. Therefore, the specific surface area of ​​96.3m2 obtained in Example 3 in Table 2 2 / g is actually the surface area provided by 0.22 grams of silica particles in one gram of modified kaolin, which is converted into a specific surface area of ​​438m 2 / g, which has reached the high end of the specific surface area of ​​silica gel. At the same time, it can also be concluded that the reaction product on the surface of kaolin is porous silica, not dense silica.

[0063] Figure 2 The figure shows the change of zeta potential with pH. In the neutral range of pH 6-8, the original kaolin is almost uncharged; adsorbents 3 and 4 are strongly negatively charged, and their surface areas are greatly improved; they can produce good adsorption effects on positively charged heavy metal ions in the solution. The zeta potential, zeta potential, and specific surface area data of the present invention are all tested by the Ningbo Institute of Materials, Chinese Academy of Sciences.

[0064] The modification method of the present invention forms inorganic silicon oxide in situ on the surface of kaolin through the sol chemical reaction of silane oxide, and adjusts the isoelectric point of kaolin to improve its adsorption and dispersion capabilities for water, ions, pigments and other substances; it can improve its adsorption capacity for heavy metal ions, thereby being used for sewage treatment; it can also enhance its adsorption of organic substances, and be used in application fields such as groundwater remediation or separation of chemicals.

[0065] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for modifying kaolin, characterized in that: The following steps are involved: adding water, ethyl silicate and kaolin under stirring, and adjusting the pH to 1.5-3.5 to obtain a first liquid; adding aqueous ammonia to the first liquid to react; After the reaction, the solid was separated by filtration, and then dried and crushed to obtain an adsorbent.

2. The modification method according to claim 1, characterized in that: The amount of ethyl silicate added is: 2-49wt%; The amount of kaolin added is: 40-50wt%; the amount of water added is: 0.6-2.5wt%; the amount of ammonia water added is: 1-2wt%.

3. The modification method according to claim 1, characterized in that: The specific steps include: 2.2 wt % of purified water, 48.1 wt % of ethyl silicate, and 48.1 wt % of kaolin were added under stirring at room temperature, and hydrochloric acid was added and stirred for 1-3 hours, and then the pH of the solution was adjusted to 1.5-3.5 to obtain a first liquid; After stirring for about 3 hours, add 1.6% ammonia water, and continue stirring for 1-2 hours; After the reaction was completed, the solid was separated by filtration and then dried and crushed to obtain an adsorbent.

4. The modification method according to claim 1, characterized in that: 1-78.1 wt% of dimethylacetamide is also added to the first liquid.

5. The modification method according to claim 4, characterized in that: The specific steps include: Add 0.6-1wt% purified water, 10-47.3wt% dimethylacetamide, 23.6-41wt% ethyl silicate, and 26.7-46wt% kaolin at room temperature with stirring, and then add hydrochloric acid to adjust the solution to pH 1.9-3 after stirring for one hour to obtain a first liquid; Continue stirring the first liquid for 5-8 hours, then let it stand for 30-40 hours, stir and add 1-1.8% ammonia water, and react for 1-2 hours; After the reaction was completed, the solid was separated by filtration and then dried and crushed to obtain an adsorbent.

6. The modification method according to claim 4, characterized in that: The specific steps include: Add dimethylacetamide and polyvinyl pyrrolidone under stirring at room temperature, and stir until the liquid becomes transparent to obtain a second liquid; Add water, ethyl silicate and kaolin at room temperature (20-30° C.) with stirring, add hydrochloric acid and stir for 2 hours, then adjust the solution to pH 3 to obtain a third liquid; After continuing to stir for about 3 hours, the second liquid and the third liquid are mixed according to a proportion, and then slowly stirred for about 13 hours to obtain a first liquid; adding aqueous ammonia to the first liquid to react; After the reaction was completed, the solid was separated by filtration and then dried and crushed to obtain an adsorbent.

7. The modification method according to claim 6, characterized in that: The second liquid contains 47-78.7 wt % of dimethylacetamide, and the balance is polyvinyl pyrrolidone; The third liquid contains 0.6-2.5wt% of water, 2-49wt% of ethyl silicate, and 40-50wt% of kaolin.

8. The modification method according to claim 6, characterized in that: The weight ratio of the second liquid to the third liquid is 0.1-0.

3.

9. An adsorbent prepared by the modification method according to any one of claims 1 to 8.

10. The adsorbent according to claim 9, characterized in that The isoelectric point of the adsorbent is pH 1.5-4.6, and the specific surface area is 35-103m 2 / g; The adsorbent is used for sewage treatment.